Ristocetin-induced Platelet Agglutination Stimulates GPIIb/IIIa-dependent Calcium Influx - Bertolino, Giampiera; Noris, Patrizia; Spedini, Pierangelo; Balduini, Carlo L (Thrombosis and Haemostasis, 1995)
We found that intracellular Ca2+ concentration i[Ca2+]i) increased during ristocetin-induced agglutination of aequorin loaded platelets resuspended in plasma. Chelation of extracellular Ca2+ had no effect on platelet clumping, but delayed and greatly reduced Ca2+ increase, indicating that it derived for the most part from Ca2+ influx. Nine monoclonal antibodies (MA) against glycoprotein (GP) Ib largely prevented ristocetin-induced platelet clumping and [Ca2+]i increase, while three anti-GPIb MA with no effect on platelet clumping did not interfere with Ca2+ movement. In unstirred samples platelet agglutination was greatly reduced and [Ca2+]i increase was abolished, suggesting that close plate- let-to-platelet contact, in addition to von Willebrand factor (vWF) binding to GPIb, is necessary for Ca2+ transient. Nine MA against GPIIb/IIIa, the gly-arg-gly-asp-ser (GRGDS) peptide and GPIIb/IIIa complex dissociation had no effect on platelet agglutination, but significantly reduced Ca2+ increase. Our results suggest that platelet clumping induced by vWF binding to GPIb is responsible for GPIIb-IIIa dependent Ca2+ influx.